Polymeric nanoparticles for selective protein recognition by using thiol-ene miniemulsion photopolymerization - KAHRAMAN, MEMET VEZİR; KAYAMAN APOHAN, NİLHAN (TAYLOR & FRANCIS LTD, 2020)
The fabrication of molecularly imprinted nanoparticles (MIP-NPs) specific for myoglobin by using thiol-ene photopolymerization in miniemulsion was described. Allyl derivatives of phenylalanine as a functional monomer was synthesized and copolymerized with acrylic monomersviaminiemulsion polymerization to produce NIP-NPs with approximately 74 nm number average particle diameter. FTIR and(1)H-NMR analysis confirmed the synthesis of functional monomer. MIP-NPs were prepared in the existence of myoglobin as a template protein. Morphological investigations exhibited that the particle size of the MIP-NPs, increased compared to the corresponding NIPs and the mean particle diameter by number was measured as 141 nm with narrow distribution. NIP-NPs that were polymerized without myoglobin were found to have less affinity to the target protein. In addition, the rebinding ability of MIP-NPs was much bigger than that of the corresponding NIPs. ELISA results showed that MIPs interact particularly with the myoglobin and show little affinity for BSA in competitive binding experiments.
Keywords: Molecularly imprinted polymer; thiol-ene polymerization; photopolymerization; myoglobin; plastic antibody; SOLID-PHASE EXTRACTION; IMPRINTED POLYMERS; PERFORMANCE; SEPARATION; LYSOZYME